2009
DOI: 10.4049/jimmunol.0900864
|View full text |Cite
|
Sign up to set email alerts
|

SHIP Represses the Generation of IL-3-Induced M2 Macrophages by Inhibiting IL-4 Production from Basophils

Abstract: There is a great deal of interest in determining what regulates the generation of classically activated (M1) vs alternatively activated (M2) macrophages (Mφs) because of the opposing effects that these two Mφ subsets have on tumor progression. We show herein that IL-3 and, to a lesser extent, GM-CSF skew murine Mφ progenitors toward an M2 phenotype, especially in the absence of SHIP. Specifically, the addition of these cytokines, with or without M-CSF, to adherence- or lineage-depleted (Lin−) SHIP−/− bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 50 publications
(38 reference statements)
3
100
0
Order By: Relevance
“…Each of these reagents has been shown to be biologically active in our hands in several different systems (20,(22)(23)(24)(25)(26), and V. Ho, M. Hamilton, and G. Krystal, unpublished results). We first determined whether cytokines that have been reported to alter Mf phenotype (i.e., IL-4, IL-13) (12) or restrict T cell proliferation (i.e., IL-10, TGF-b) (27) were involved.…”
Section: Mfs Suppress T Cell Proliferation Via Ifn-g-induced No Produmentioning
confidence: 73%
“…Each of these reagents has been shown to be biologically active in our hands in several different systems (20,(22)(23)(24)(25)(26), and V. Ho, M. Hamilton, and G. Krystal, unpublished results). We first determined whether cytokines that have been reported to alter Mf phenotype (i.e., IL-4, IL-13) (12) or restrict T cell proliferation (i.e., IL-10, TGF-b) (27) were involved.…”
Section: Mfs Suppress T Cell Proliferation Via Ifn-g-induced No Produmentioning
confidence: 73%
“…Furthermore, we show that SHIP-1 2/2 mice are prone to autoimmunity, and that conditional loss of SHIP-1 in B cells is sufficient to cause disease; however, severity of disease is influenced by genetic background. The lung disease in young SHIP-1 2/2 mice is thought to be caused by macrophages that are skewed toward an alternatively activated (M2) phenotype, due to the hyperresponsiveness of SHIP-1 2/2 macrophage progenitors during differentiation in combination with elevated levels of M2-skewing cytokines (3,4,9,10,28,29). C57BL/6 background, but not BALB/c background SHIP-1 2/2 mice show elevated levels of Th2 and proinflammatory cytokines in serum and in BAL fluid, suggesting that aberrant cytokine production is driving the lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…IL-3-mediated signals in basophils are reportedly involved in the ITAM in the FcRg-spleen tyrosine kinase-ERK pathway to produce IL-4 and the IL-3Rbc-JAK-STAT5 pathway to promote proliferation and differentiation (30,36,37). Recently, it was shown that SHIP inhibited IL-4 production from basophils (42). In addition, Src homology 2 domain-containing protein tyrosine-phosphatase 1 (SHP-1) can interact with and inhibit the phosphorylation of STAT5 (43,44).…”
Section: Discussionmentioning
confidence: 99%